Racial Profiling amidst Geopolitical Tension: Chinese Faculty in Canada - Zha, Qiang; Li, Xiaojie (International Higher Education, 2024)
Our survey reveals that Chinese-origin faculty in Canadian universities used to work in the frontiers of collaborating with China, leveraging their cultural and linguistic competencies, as well as personal networks. Now, they are caught in geopolitical conflicts and even become victims of implicit or explicit racial profiling, as a result of policies that link research collaboration with China to national security concerns.